Characterization of Trichuris muris secreted proteins and extracellular vesicles provides new insights into host–parasite communication. Issue 1 (21st January 2018) - Eichenberger, Ramon M.; Talukder, Md Hasanuzzaman; Field, Matthew A.; Wangchuk, Phurpa; Giacomin, Paul; Loukas, Alex; Sotillo, Javier
ABSTRACT: Whipworms are parasitic nematodes that live in the gut of more than 500 million people worldwide. Owing to the difficulty in obtaining parasite material, the mouse whipworm Trichuris muris has been extensively used as a model to study human whipworm infections. These nematodes secrete a multitude of compounds that interact with host tissues where they orchestrate a parasitic existence. Herein we provide the first comprehensive characterization of the excretory/secretory products of T. muris . We identify 148 proteins secreted by T. muris and show for the first time that the mouse whipworm secretes exosome‐like extracellular vesicles (EVs) that can interact with host cells. We use an Optiprep® gradient to purify the EVs, highlighting the suitability of this method for purifying EVs secreted by a parasitic nematode. We also characterize the proteomic and genomic content of the EVs, identifying >350 proteins, 56 miRNAs (22 novel) and 475 full‐length mRNA transcripts mapping to T. muris gene models. Many of the miRNAs putatively mapped to mouse genes are involved in regulation of inflammation, implying a role in parasite‐driven immunomodulation. In addition, for the first time to our knowledge, colonic organoids have been used to demonstrate the internalization of parasite EVs by host cells. Understanding how parasites interact with their host is crucial to develop new control measures. This first characterization of the proteins and EVs secreted by T. muris provides important information on whipworm–host communication and forms the basis for future studies.